Online Learning in Civic Education Research Trend: A Bibliometric Analysis - Sulkipani, Sulkipani; Komalasari, Kokom; Sapriya, Sapriya; Fitriasari, Susan; Blegur, Jusuf (International Review of Research in Open and Distributed Learning, 2025)
Online learning in civic education (OLCE) has been going on since the 2000s. It has become an increasingly interesting topic in light of recent technological advances and emergencies, and it contributes to improving the quality of learning processes and outcomes. This study aimed to track the publication trends of OLCE in the Scopus database (2005–2024). The method used was bibliometric, with VOSviewer software analysis. The investigation found 123 documents, half of which were articles, and the rest distributed among conference papers, book chapters, conference reviews, books, and notes. These publications were written by 320 authors from 39 different countries and used nearly 800 keywords. The number of OLCE publications increased significantly in 2021 and reached its highest peak in 2024. VOSviewer analysis showed that civic education was connected to the keywords “online learning” and “e-learning” in the case of large nodes and close distances. However, other strategic keywords, such as “MOOC,” “digital citizenship,” “artificial intelligence,” and “social media” were detected in small nodes and far distances. The keyword “global citizenship education” was not directly connected; even “ChatGPT,” the most influential OpenAI today, was not seen at all. This could mean that the development of several strategic keywords would make for a potential research study in future. This research provides new insights for researchers and institutions involved in OLCE publication mapping for future development.